The Moderating Effect of Treatment Engagement on Fear-avoidance Beliefs in People With Chronic Low Back Pain. Issue 12 (12th December 2021) - Marshall, Paul W.; Morrison, Natalie M.V.; Mifsud, Annaleise; Gibbs, Mitchell; Khan, Naseeb; Meade, Tanya
Abstract : Objectives: The fear-avoidance model (FAM) is used to explain pain-related disability and design targeted interventions for people with chronic low back pain. While treatment engagement is critical, it is unknown how treatment moderates the FAM. Methods: This study examined whether pathways within the FAM were moderated by treatment engagement in 508 people with chronic low back pain. Measures of disability, pain, fear, catastrophizing, anxiety, depression, and self-efficacy were collected through self-report, and descriptors of treatment engaged within the last month (physical activity type, medication, allied and medical health practitioner). Moderated mediation analyses were performed to examine the conditional effect of treatment engagement on fear-avoidance pathways. Results: The conditional effect of anxiety on disability was only significant for people who did not report any treatment engagement in the last month ( B =1.03, 95% confidence interval: 0.53-1.53, P <0.001). The effect of depression increased for people reporting more different types of treatment in the last month (1 level of treatment increase, B =0.27, 95% confidence interval: 0.05-0.50, P =0.019). Conversely, greater treatment engagement had a positive influence on the mediating effect of self-efficacy. That is, the effect of pain on efficacy reduced with greater treatment engagement, with a concomitant increased effect of self-efficacy on disability. Discussion: Clinicians should explore the history and rationale behind patient treatment seeking behavior to ensure this is not reinforcing the negative effects of depressive symptoms on pain-related disability.